A limb-specific strategy across a range of running speeds in transfemoral amputees - Sakata, H.; Hashizume, S.; Takemura, H.; Hobara, H. (Medicine & Science in Sports & Exercise, 2020)
Purpose: This study investigated the vertical ground reaction force (vGRF) variables and spatiotemporal parameters related to running speed across a range of speeds in sprinters with unilateral transfemoral amputation who used running-specific prostheses (RSPs). Methods: Ten sprinters with unilateral transfemoral amputation ran on an instrumented treadmill at incremental speeds of 30%, 40%, 50%, 60%, and 70% of the average speed of their 100-m personal best (100%) while using their RSPs. The vGRF data were collected at 1000 Hz during each trial. We calculated the vGRF variables and spatiotemporal parameters, including the stance average vGRF (Favg), step frequency (Freqstep), and contact length (Lc; the length traveled by a runner`s body during the stance phase). Results: All three mechanical variables related to speed (Favg, Freqstep, and Lc) were similar for both the unaffected and affected limbs at relatively slower speeds, and these variables increased with speed for each limb. Although Freqstep remained similar between the limbs at relatively faster speeds, the affected limb exerted 11% smaller Favg and showed 12% longer Lc than the unaffected limb. Conclusion: These results suggest that, in order to achieve a faster running speed, runners with unilateral transfemoral amputation using RSPs likely adopt limb-specific biomechanical strategies for the unaffected and affected limbs, where the smaller Favg of the affected limb would be compensated by the longer Lc of the affected limb, without achieving a higher Freqstep.